T cell therapy of B-CLL lymphoma against CD20 alternative splice variant: in vitro experiments : T cell therapy of B-CLL lymphoma - Chegni, Hamid; Hassan, Zuhair; Babaii, Hadis (Archives of Advances in Biosciences, 2021)
Introduction: Cancer immunotherapy has become a major player in modern oncology. In immunotherapy, immune cells selectively recognize and kill cancerous cells; this way, many side effects of chemotherapy and radiotherapy are reduced. One of the immunotherapy methods is the T cell therapy, which is based on the use of T cells with determined antigenic specificity for cancer cells. The search for unique tumor antigens which are specific to malignant cells and have the ability to stimulate cellular immunity is one of the main targets of malignancies treatment. Materials and methods: D393-CD20 is an alternative splicing form of the CD20 surface receptor, which lacks 168 nucleotides in exons 3 to 7 of the CD20 sequence. D393-CD20 peptide is merely expressed on cancerous B cells, such as Burkitt’s lymphoma (BL), DLBCL and B-CLL. In this study we isolated and expanded a CD8+ T lymphocyte specific clone for a D393-CD20 antigen to examine the effect on B-CLL cell line. To this end, we evaluated the impact of cytotoxic T cells upon D393-CD20 antigen, expressed on malignant B cells. We also evaluated the ratio of apoptosis using flow cytometry and MTT. Results: Results suggest that targeting D393-CD20 antigen with specific CD8+ T lymphocytes is very effective in preventing tumor cells growth. Conclusion: Targeting D393-CD20 can be a proper choice for B-cell lymphoma immunotherapy.